GAMBARAN KUALITAS HIDUP PADA INDIVIDU YANG MENGALAMI KERAUHAN - Bagus Ari Nugraha Suela; Yohanes Kartika Herdiyanto (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2017)
Quality of life’s aspect on every individual will be vary. One of the important experiences that may change Balinese’s people life is when they have an event called as kerauhan. Kerauhan is a term used to address a certain situation when someone is believed or taken as being possessed by a soul, other than the soul that has been living that body since it was born (Swadiana & Putrawan, 2006). There will be some changes occurred in someone’s life aspect which affects the achievements on their life by experienced kerauhan. Based on this, researchers wanted to know the picture of someone’s life-quality who experienced kerauhan. The qualitative research method with phenomenological approach is used in this research to describe the aspects of life that got affected someone’s life who have experienced kerauhan. The data collection that is used in this research is an in-depth interview and observation which were examined toward 5 Balinese individuals of two categories. Individuals with a kerauhan experience based on intentional purposes such as ritual purposes, falls under the first category. While individuals who had an unexpected kerauhan, falls under the second category. The result of this research shows that kerauhan doesn’t have a direct impact on someone’s life quality. But kerauhan can increase or decrease some aspects of someone’s life which at the end would change that person’s life into a better or even a disadvantageous one. Detailed result will be discussed under the context of the aspects of life that are affected by kerauhan. Keyword: possession-trance, kerauhan, quality of life aspect, Balinese